2015
DOI: 10.1002/pat.3631
|View full text |Cite
|
Sign up to set email alerts
|

In situsynthesis of a novel transparent poly (methyl methacrylate) resin with markedly enhanced flame retardancy

Abstract: A novel phosphorus-containing monomer, (6-oxido-6H-dibenzo [c,e][1,2]oxaphosphinin-6-yl)methyl acrylate (DOPO-AA), is first synthesized and characterized by Fourier transform infrared spectra (FTIR), 1 H nuclear magnetic resonance (NMR) and 31 P NMR. The monomer is then introduced into poly (methyl methacrylate) (PMMA) matrix via in situ copolymerization to produce a new PMMA based copolymer (PMMA/DOPO-AA). From UV-vis spectra, microscale combustion calorimeter (MCC) and thermogravimetric analyses (TGA) result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…The broader absorption peak of PMMA‐co‐BDPA at approximately 3435 cm −1 is attributable to the hydroxyl in the char layers, which may originate from phosphoric acid and other substances that decompose during the combustion of the copolymer. The absorption peak of PH can be clearly observed at 2355 cm −1 , and the peak appearing at approximately 1625 cm −1 indicates the formation of polyaromatic carbons . In addition, the peaks at 1397 and 1117 cm −1 are the corresponding peaks of PO and PO, respectively.…”
Section: Resultsmentioning
confidence: 94%
“…The broader absorption peak of PMMA‐co‐BDPA at approximately 3435 cm −1 is attributable to the hydroxyl in the char layers, which may originate from phosphoric acid and other substances that decompose during the combustion of the copolymer. The absorption peak of PH can be clearly observed at 2355 cm −1 , and the peak appearing at approximately 1625 cm −1 indicates the formation of polyaromatic carbons . In addition, the peaks at 1397 and 1117 cm −1 are the corresponding peaks of PO and PO, respectively.…”
Section: Resultsmentioning
confidence: 94%
“…With the introduction of MMA, HRR peak value is shifted to higher value while THR value decreases slightly. For example, Jiang et al produced a new PMMA‐based copolymer with a novel phosphorus‐containing monomer (DOPO‐AA), and it is concluded that the HRR peak and THR of PMMA copolymer were 192.0 W/g and 17.1 kJ/g when 10.0 wt% DOPO‐AA was added, respectively. Compared to these data, PUPE and UPE + MMA50% copolymer possess lower HRR and THR values.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, DOPO‐based monomers have been used to prepare matrices with chemically bound flame‐retardant groups (reactive strategy) by step polymerization, like epoxy resins, polyurethane, poly(ethylene terephthalate), polyamide, ethylene‐vinyl acetate copolymer, and polysulfone . Nevertheless, to the best of our knowledge, only one study has been reported about the synthesis and application of DOPO‐derived acrylate monomer for the preparation of flame resistant thermoplastic matrix by free radical polymerization . More precisely, the latter monomer was first derived from acryloyl chloride with DOPO covalently linked as side group, then copolymerized with methyl methacrylate (MMA).…”
Section: Introductionmentioning
confidence: 99%